How glycogen sustains brain function: A plausible allosteric signaling pathway mediated by glucose phosphates. Issue 8 (August 2019) - DiNuzzo, Mauro
Astrocytic glycogen is the sole glucose reserve of the brain. Both glycogen and glucose are necessary for basic neurophysiology and in turn for higher brain functions. In spite of low concentration, turnover and stimulation-induced degradation, any interference with normal glycogen metabolism in the brain severely affects neuronal excitability and disrupts memory formation. Here, I briefly discuss the glycogenolysis-induced glucose-sparing effect, which involves glucose phosphates as key allosteric effectors in the modulation of astrocytic and neuronal glucose uptake and phosphorylation. I further advance a novel and thus far unexplored effect of glycogenolysis that might be mediated by glucose phosphates.